Evaluation of the effect of different organic solvents in the efficiency of the recovery of pullulan synthesized by Aureobasidium pullulans - Lisboa, Gustavo Henrique; Pena, Aline de Cassia Campos; Rodrigues, Andre [UNESP]; Rodrigues, Sabrina Ávila (Taylor & Francis, 2025)
The production and extraction of microbial biopolymers face significant challenges, especially during the purification process. This study evaluated the production of pullulan under controlled conditions and its extraction using different organic solvents. Kinetic parameters such as cell growth rate, substrate consumption, biomass production and biopolymer yield were analyzed. Fermentation was conducted in a bioreactor, followed by solvent extraction of different chemical groups, including ketones, benzene, carboxylic esters, alkanes, and cycloalkanes. The production of the biopolymer started with 10 g/L after 15 hours of fermentation and reached 12 g/L at the end of the process. However, extraction using solvents such as Cyclohexane, Hexane, and Toluene was not effective due to inappropriate molecular interactions. On the other hand, Isopropyl Alcohol recovered 18.87 g/L of pullulan while Ethanol reached 12.82 g/L. Despite the higher yield with Isopropyl Alcohol, Ethanol stood out as the best alternative due to its low toxicity, reduced cost, and ease of handling. The results showed that Ethanol is optimal for the extraction process. Still, it represents a practical approach to the recovery of this biopolymer.
Keywords: biopolymers; Black yeast; exopolysaccharide; organic solvents